1983
DOI: 10.1037/0022-0663.75.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of computer-based teaching on secondary school students.

Abstract: This article used quantitative techniques, or meta-analysis, to integrate findings from 51 independent evaluations of computer-based teaching in Grades 6 through 12. The analysis showed that computer-based teaching raised students' score^ on final examinations by approximately .32 standard deviations, or from the 50th to the 63rd percentile. Computer-based instruction also had smaller, posi'tive effects on scores on follow-up examinations given to students several months after the completion of instruction. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
106
1
21

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(139 citation statements)
references
References 9 publications
11
106
1
21
Order By: Relevance
“…A. Kulik, Bangert, and Williams (1983) and by C. C. Kulik, J. A. Kulik, and Cohen (1980a) has shown that although such effects have confounded findings at the secondary school level, this problem is not evident in studies involving college students.…”
Section: Discussionmentioning
confidence: 92%
“…A. Kulik, Bangert, and Williams (1983) and by C. C. Kulik, J. A. Kulik, and Cohen (1980a) has shown that although such effects have confounded findings at the secondary school level, this problem is not evident in studies involving college students.…”
Section: Discussionmentioning
confidence: 92%
“…While some researchers have concluded that the use of computers does raise student achievement (e.g., Kulik, Bangert, & Williams, 1983), others have concluded that a computer is a vehicle that delivers instruction but does not in and of itself affect student achievement (Clark, 1983). While computer-assisted instruction is most often used within drill-and-practice situations aimed at memorizing basic facts and increasing the quantity of production, there is hope that an increased use of computer-assisted instruction in more complex learning situations will increase students' ability to apply their knowledge and solve problems.…”
Section: Effects Of Cooperativementioning
confidence: 99%
“…Many studies fail to identify and manipulate specific media attributes and therefore miss the goal of demonstrating their differential effects. Novelty is one important source of confounding effects in past studies, with research showing a decrease in student outcome differences between media and conventional treatments over time (Kulik, Bangert, and Williams 1983). Any technology might improve learning only because it generally requires the instructor to rework and rethink his or her instructional materials, and the novelty might engage learners.…”
Section: Utility and Effectiveness Of Media In Educationmentioning
confidence: 99%